An evaluation of the interior design of selected housing units in the Bistekville 1 Resettlement housing project based on the principles of universal design - Avandfarjad, Sepideh; Mayo, Adelaida V. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT This study which utilized Descriptive Analysis for its research design, sought to determine whether interior design strategies have been incorporated by the Quezon City local government in the construction of the Bistekviille 1 Resettlement Housing Project in Quezon City. It also made an attempt to evaluate the interior design of selected housing units in Bistekville 1 based on the principles of Universal Design. Purposive sampling was used in choosing the three respondents for the interviews conducted for the study, involving a local government representative and two homeowners of selected units in Bistekville 1. Likewise, two sample housing units representing the two housing types found in Bistekville 1 namely, the loft-type and one-storey type, were purposively chosen for the observations conducted during the data gathering and for purposes of evaluation of their interior design. Data gathered from the interviews and observations were analyzed using the National Building Code and the principles of Universal Design as bases for evaluation. Results and findings indicate that no interior design strategies were used in the construction of the Bistekville 1 community, and interior design improvements need to be made to enhance the efficiency of the resettlement housing projects of the local government in terms of safety, mobility and accessibility. The study recommends that the University of the Philippines DilimanCollege of Home Economicsthrough its Department of Clothing, Textiles & Interior Design, use its partnership with the Quezon City local government as an avenue to offer interior design services to the beneficiaries of its resettlement housing projects. Future similar studies are also recommended, involving other resettlement sites constructed for urban poor families and survivors of natural disasters.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Bistekville Resettlement Housing Project -- Decoration; Housing project -- Philippines -- Quezon City -- Decoration